Peningkatan Kewaspadaan Risiko Malnutrisi Siswa SDN 133888 Kelurahan Pasar Baru Kota Tanjungbalai Melalui Pemantauan Status Gizi dan Sosialisasi Isi Piringku - Lubis, Nenni Dwi Aprianti; Amelia, Sri; Rohmawati, Lili; Adha, Kasa Rullah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
Child health is a crucial issue for the future of the nation, where nutrition is a major concern. Nutritional disorders in children can lead to obesity, learning disabilities, developmental disorders, chronic diseases, and cancer, influenced by genetic factors, socio-economics, parental education, history of infection, and intake patterns. Anthropometric measurements are used to detect these disorders. This community service activity aims to provide socialization about balanced nutrition through the concept of “Isi Piringku” and prevention of helminthiasis, as well as measuring the nutritional status of 316 students of SD Negeri 133888. The results showed that 87% of students had good nutritional status, while 13% had nutritional disorders, consisting of 5.4% undernutrition, 3.8% overnutrition, and 3.8% obesity. Further research is needed to identify factors that contribute to these nutritional disorders, so that appropriate interventions in community service activities can be designed to reduce the prevalence of malnutrition in the future.